Monitoring the Future: Restricted-Use Panel Data, United States, 1976-2019 - Schulenberg, John E. ([Verlag nicht ermittelbar], 2018)
The Monitoring the Future (MTF) project is a long-term epidemiologic and etiologic study of substance use among the nation's youth and adults. It is conducted at the University of Michigan Institute for Social Research, funded by a series of investigator-initiated research grants from the National Institute on Drug Abuse. From its inception in 1975, the project has collected data annually from nationally representative samples of 13,000-19,000 high school seniors, located in approximately 135 schools nationwide (i.e. cross-sectional data). Beginning in 1991, similar surveys of nationally representative samples of 8th and 10th graders have been conducted annually. In all, approximately 45,000 students annually respond to about 100 drug use and demographic questions, as well as to about 200 additional questions divided among multiple forms on other topics such as attitudes toward government, social institutions, race relations, changing gender roles, educational aspirations, occupational aims, and marital plans. The MTF project also includes a longitudinal panel study component. Beginning with the class of 1976, biennial follow-up mail surveys have been conducted with representative subsamples of respondents from each senior year class, spanning modal ages 19 to 30. From each senior year cohort, a sample of about 2,450 students are selected for longitudinal follow-up. The sample is randomly split into two halves (approx. 1,225 each) to be followed every other year. One half-sample begins its first follow-up the next year at modal age 19, and the other half-sample begins its first follow-up in the second year at modal age 20. The follow-ups continue such that the modal ages are as follows: FU1=19/20, FU2=21/22, FU3=23/24, FU4=25/26, FU5=27/28, FU6=29/30. Respondents receive the same survey form for follow-up as they completed at base year. When the 12th grade respondents originally selected for follow-up reach age 35, attempts are made to contact all respondents who were selected into the panel from 12th grade. Respondents continue to be surveyed every five years at ages 35, 40, 45, 50, 55, and 60. Single questionnaires are presented at each age, covering many of the same topics as the age 19-30 surveys and including additional questions on life events, drug use, and health. More information about the MTF project can be accessed through the Monitoring the Future website - including the purpose, design, sampling procedures, and questionnaire administration; selected data tables and figures; a listing of publications and press releases; information about the research investigators; and links to related websites.